2008
DOI: 10.1021/ja076668w
|View full text |Cite
|
Sign up to set email alerts
|

Copper Complexes of Anionic Nitrogen Ligands in the Amidation and Imidation of Aryl Halides

Abstract: Copper(I) imidate and amidate complexes of chelating N,N-donor ligands, which are proposed intermediates in copper-catalyzed amidations of aryl halides, have been synthesized and characterized by X-ray diffraction and detailed solution-phase methods. In some cases, the complexes adopt neutral, three-coordinate trigonal planar structures in the solid state, but in other cases they adopt an ionic form consisting of an L 2 Cu + cation and a CuX 2 − anion. A tetraalkylammonium salt of the CuX 2 − anion in which X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
234
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(257 citation statements)
references
References 67 publications
20
234
1
2
Order By: Relevance
“…Moreover, we have conducted computational studies by DFT on the energy of a phen-ligated arylcopper(III) halide phenoxide complex, and the ΔG for formation of this species from the [Cu(phen)(OPh)] and PhI is computed to be 22.1 kcalmol −1 [Eq. (10)]. This energy is consistent with the barrier corresponding to the conditions of the experiments in Eq.…”
Section: The Reaction Of O-(allyloxy)iodobenzene With the P-cresolatesupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, we have conducted computational studies by DFT on the energy of a phen-ligated arylcopper(III) halide phenoxide complex, and the ΔG for formation of this species from the [Cu(phen)(OPh)] and PhI is computed to be 22.1 kcalmol −1 [Eq. (10)]. This energy is consistent with the barrier corresponding to the conditions of the experiments in Eq.…”
Section: The Reaction Of O-(allyloxy)iodobenzene With the P-cresolatesupporting
confidence: 86%
“…[9] Only recently have any isolated copper complexes been evaluated as intermediates in copper-catalyzed coupling reactions. [10,11] In one recent study, copper(I) imidates and amidates were isolated in pure form, structurally characterized, and shown to be intermediates in related copper-catalyzed Goldberg reactions, [10] and in another study kinetic data were obtained on copper amidates generated in situ. [12,13] The relationship between intermediates in copper-catalyzed coupling reactions that form C-N bonds and potential intermediates in couplings that form C-O bonds is unknown.…”
mentioning
confidence: 99%
“…Calculated free energy barriers for free radical formation are very high (93 kcal/mol). It is much higher than energy barrier reported for OA pathway [18]. Calculated free energy indicates that the oxidation of Cu(I) through free radical pathway is not possible.…”
Section: Generation Of Nucleophile Ligated Inert [Cu(nu) 2 ] -Speciesmentioning
confidence: 64%
“…Hartwig and co-workers [18] have demonstrated that species A do not participate in reactions. It was proposed that species A are inert off cycle species and responsible for deactivation of copper and high demand of Cu/ligand system.…”
Section: Generation Of Nucleophile Ligated Inert [Cu(nu) 2 ] -Speciesmentioning
confidence: 99%
“…They clearly showed that the aryl halide activation occurs by the [(L)Cu I (Nu)] complexes. In this regard, Hartwig et al were able to isolate and characterize a number of copper imidate, amidate, amino, phenoxide, and thiophenoxide complexes which are chemically competent to couple a variety of aryl halides [40,42,56]. The studies carried out on the reactivity of these complexes, including kinetic studies and radical clock experiments, argued against pathways involving radical intermediates.…”
Section: Introductionmentioning
confidence: 99%